2021
DOI: 10.1016/j.amjcard.2020.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Prolonged Pacemaker Dependency After Cardiac Surgery to Mortality

Abstract: on behalf of the GIROC Investigators Permanent pacemaker implantation (PPI) represents a rare complication after cardiac surgery, with no uniform agreement on timing and no information on follow-up. A multicenter retrospective study was designed to assess pacemaker dependency (PMD) and longterm mortality after cardiac surgery procedures. Between 2004 and 2016, PPI-patients from 18 centers were followed. Time-to-event data were evaluated with semiparametric regression Cox models and semiparametric Fine and Gray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Conduction defects are common complications following open-heart surgeries, approximately appearing in 10–15% of patients undergoing open-heart surgeries [ 1 3 ]. The lowest incidence of such a complication is seen after CABG, while valvular surgery provides the highest prevalence of permanent pacemaker implantation (PPI) [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conduction defects are common complications following open-heart surgeries, approximately appearing in 10–15% of patients undergoing open-heart surgeries [ 1 3 ]. The lowest incidence of such a complication is seen after CABG, while valvular surgery provides the highest prevalence of permanent pacemaker implantation (PPI) [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, pacemaker dependency after device implantation may also play an important role in distant survival. 6 The work by Bianco and colleagues 7 from the University of Pittsburgh presented in the current issue of the Journal adds valuable data to this controversy and suggests that when adjusted for patient characteristics, PPM implantation after isolated valve or valve and coronary surgery does not affect distal survival. Although the authors present a large clinical cohort, the results and conclusions of the study need to be evaluated through a prism of several methodologic limitations.…”
mentioning
confidence: 98%
“…This policy might reduce health costs, patient discomfort, and most of all improve survival, as pacemaker implantation has been considered a potential risk factor for poor survival at follow-up. 4 Second, balloon-expandable valves should be considered over self-expandable valves in those patients with such risk factors as right BBB, small annuli, and calcified aortic valves.…”
mentioning
confidence: 99%
“…3 A multicenter retrospective analysis of 859 patients requiring PPI after cardiac surgery found that found that 30% were pacemaker-independent at 6 months. 4 Interestingly, pacemaker dependency was associated with an increased risk of long-term mortality. This information raises some doubts regarding the correct timing for PPI.…”
mentioning
confidence: 99%
See 1 more Smart Citation